IDENTIFIKASI JAMUR MIKROSKOPIK DARI TAMBAK UDANG Litopenaeus vannamei SISTEM SEMI-INTENSIF - Lisnawati Sinaga; Rahmad Lingga; Budi Afriyansyah; Mu'alimah Hudatwi (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2020)
Litopenaeus vannamei is one of the most common shrimp species cultivated with the semi-intensive system in Indonesia. This system required large food and probiotic input during cultivation and certainly will impact the water quality and the presence of the microbial colony. The unhealthy water circulation will increase microbe pathogen. Fungi is one of ubiquitous microbe that often appears in shrimp pond. The aim of this study is to identify and calculate the biology index from shrimp cultivation ponds. This research was implemented in March 2019 – April 2020. The method of this research is purposive sampling to get the fungi culture from inlet, outlet and rejuvenate shrimp ponds. The identification of fungi was done with macroscopic and microscopic examination. The result found 9 isolates fungi comprised of 8 species. There were 4 fungi identified from the inlet shrimp pond, Aspergillus sp 1, Aspergillus sp 4, Penicillium sp, and Trichoderma sp 2, while from outlet pond were Aspergillus sp 1, Trichoderma sp 1 and from rejuvenating shrimp ponds were Saccharomyces cerevisiae, Trichoderma sp 1 and Penicillium sp. There were no fungi found from L. vannamei, because all of the L. vannamei shrimp in healthful condition.